Preliminary analysis on the use of Trophic State Indexes in a brazilian semiarid reservoir - Paulo de Freitas Lima; Mart Som Reis Sousa; André Ferreira Porfírio; Beatriz Soares Almeida; Rogério Herlon Furtado Freire; Sandra Tédde Santaella (Acta Scientiarum. Biological Sciences, 2015)
The Carlson’s (1977) Trophic State Index (TSI) is a widely employed tool to estimate the degree of eutrophication in a reservoir. In Brazil, the need of a classification system that would take into account regional characteristics employed adjusted indexes generated by data from reservoirs in the southeastern region of the country. Current research compares responses for Carlson’s TSI (1977) and its derivations for Brazilian reservoirs from data collected in the Pereira de Miranda Reservoir (State of Ceará, Brazil), and analyzes the influence of local conditions on results and their applicability to reservoirs in the semiarid region. TSIs were calculated by data on total phosphorus, chlorophyll a and water transparency. The reservoir was estimated as mesotrophic based on the chlorophyll a variable, and between eutrophic and hyper-eutrophic when based on total phosphorus data and water transparency. Results showed the need to consider intrinsic factors in the discussion on the applicability of TSIs to reservoirs in the semiarid region since the peculiar hydro-climatic conditions and morphometric characteristics make them even more vulnerable to disturbance agents, such as winds which have a significant influence on processes that determine the trophic state.